Representing violence in France 1760-1820 - Wynn, T (Voltaire Foundation, 2017)
Violence was an inescapable part of people’s daily lives in eighteenth-century France. The Revolution in general and the Terror in particular were marked by intense outbursts of political violence, whilst the abuse of wives, children and servants was still rife in the home. But the representation of violence in its myriad forms remains aesthetically troublesome. Drawing on correspondence, pamphlets, novels and plays, authors analyse the portrayal of violence as a rational act, the basis of (re)written history, an expression of institutional power, and a challenge to morality. Contributions include explorations of: • the use of the dream sequence in fiction to comprehend violence; • how rhetoric can manipulate violent historical truth as documented by Burke in his Reflections on the Revolution in France; • the political implications of commemorating the massacre at the Tuileries of 10 August 1792; • how Sade’s graphic descriptions of violence placed the reader in a morally ambivalent position; • the differing responses of individuals subjected to brutal incarceration at Vincennes and the Bastille; • the constructive force of violence as a means of creating a sense of self. Thomas Wynn, Introduction I. Violence and the crisis of reason John Dunkley, Gambling and violence: Loaisel de Tréogate as a neuroscientist? Olivier Ritz, Metaphors of popular violence in the Revolutionary debate in the wake of Edmund Burke Stéphanie Genand, Dreaming the Terror: the other stage of revolutionary violence Pierre Saint-Amand, Gothic explosions: Révéroni Saint-Cyr’s Pauliska ou La Perversité moderne II. Violence and the (re)writing of history Catriona Seth, The ‘dix août’ (10 August 1792) in literary texts Michèle Vallenthini, Violence in history and the rise of the historical novel: the case of the marquis de Sade Yann Robert, The everlasting trials of Jean Calas: justice, theatre and trauma in the early years of the Revolution Pierre Frantz, Violence in the theatre of the Revolution III. Violence and institutions Thomas Wynn, Violence, vulnerability and subjectivity in Sade Odile Jaffré-Cook, The Bastille or the ‘Enfer de Dutailli de Saint-Pierre’ Ourida Mostefai, Violence, terrorism and the legacy of the Enlightenment: debates around Jean-Jacques Rousseau and the Revolution IV. Violence and morality Malcolm Cook, Violence in the work of Bernardin de Saint-Pierre Rebecca Sopchik, Violence and the monster: the Private lives of the duc d’Orléans Jean-Christophe Abramovici, ‘Avec une telle violence que…’: Sade’s use of the term violence Will McMorran, The sound of violence: listening to rape in Sade Michel Delon, Violence in the novels of Charlotte [de] Bournon-Malarme Summaries Bibliography Index